(In)Visible signs of gender-based violence - Wagner, Anne; Condello, Angela (Gender, justice and legal feminism, 2025)
The edited volume explores the causes, forms, and cultures of gender-based violence in society, including how children are educated, how games, art and even language promote differences, stereotypes, neutrality between men and women. It is a place to reflect on the growing importance of tolerance, diversity and acceptance of others. The book focuses on many facets, whether in a confined or public space, with a series of empirical and theoretical chapters from around the world. The volume provides key contemporary commentary on the changing dynamics of gender-based violence. It unveils a range of contexts and spaces in which gender-based violence happens, showcasing its scale and impact worldwide. The discussions presented in the book encourage a critical reflection on the global pandemic of gender-based violence, prompting a vital question about the sufficiency and effectiveness of responses to this global crisis (Professor Olga Jurasz, The Open University Law School).